Automated quantification of Ki-67 proliferative index of excised neuroendocrine tumors of the lung - Liu, Sandy Z (BioMed Central, 2014)
BACKGROUND: The histopathologic distinction between typical carcinoid (TC) and atypical carcinoid (AC) of the lung is based largely on mitotic index. Ki-67 may aid in separation of these tumors, as well as the distinction from large cell neuroendocrine carcinoma (LCNEC). METHODS: We identified 55 surgically resected primary neuroendocrine lung tumors (39 TC, 7 AC, 9 LCNEC) based on mitotic rate and histologic features. Ki-67 proliferative index based on automated image analysis, tumor necrosis, nodal metastases, local or distant recurrence, and survival were compared across groups. RESULTS: The mean mitotic count and Ki-67 index for TC, AC, and LCNEC were 0.1 and 2.3%, 3.4 and 16.8%, and 56.1 and 81.3% respectively. The Ki-67 index did not overlap among groups, with ranges of 0–6.7% for TC, 9.9-25.7% for AC, and 63.2-91.9% for LCNEC. Nodal metastases were identified in 4/39 (10%) TC, 2/7 (22%) AC, and 2/8 (25%) LCNEC. There was no survival difference between TC and AC, but there was a significant survival difference between LCNEC and TC and AC combined (p < 0.001). There was a step-wise increase in disease free survival with tumor grade: no TC recurred, 2/7 AC recurred or progressed (median interval 35.5 months), and all LCNEC recurred or progressed (median interval 10.1 months). No patient with TC or AC died of disease, compared to 7/8 LCNEC with follow-up data. CONCLUSIONS: We conclude that Ki-67 index is a useful diagnostic marker for neuroendocrine tumors, with 7% a divider between AC and TC, and 50% a divider between LCNEC and AC. LCNEC is biologically different from AC and TC, with a much more aggressive course, and a high Ki-67 index. VIRTUAL SLIDES: The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/13000_2014_174